A coherent growth policy for Macedonia - Tevdovski, Dragan (Fridrich Ebert Stiftung, 2018)
 Macedonia implemented the neoliberal economic model through the transition process. It is characterized by the reduction of the workers’ rights, destroyed power of trade unions, existence of flat and low taxation, glorification of the foreign direct investments (FDI) and progressive replacement of the public health and educational system with private. This model failed to achieve the productivity growth and solution for unemployment, while it increases the income inequality in the country.  The wage-led growth strategy could be solution for economic development of Macedonia. It is opposite than the two dominant neoliberal strategies: export-led growth and debt-led growth. Moreover, there is need for introduction of fair taxation and re-build of social safety net. EU should start to promote the element of the famous European social market model through the country’s integration process.  European Commission in the last report about Macedonia used the term: “captured state”. The first step towards deconstruction of the abused institutions by the political elites is fiscal transparency. It should be accompanied by liberation of the control mechanisms over the people in power: strong parliament, depoliticized police, independent judiciary, free media and powerful civil sector.